SMRITI (MEMORY) MEDITATION: A TOOL FOR DIAGNOSIS AND THE MANAGEMENT OF PSYCHOSOMATIC SYMPTOMS: A CLINICAL OBSERVATION STUDY - Dilipkumar, K.V. (International Journal of Ayurveda and Pharma Research, 2016)
Web of causation of diseases are well narrated in Ayurveda classics. Intellectual error is identified as major cause of diseases and its role in the manifestation of psychosomatic diseases is well explained in Charakasamhita. Smriti, exploration of memory is suggested as one of the five components of psychotherapeutic techniques in the managing the psychic components of diseases. Method A modified version of Smriti is developed as a guided – interactive meditation and tested for its therapeutic efficacy. A clinical observational study conducted in 104 patients is reported in this article. Subjective revelation during the meditation, somatic experience and relief of symptom were used as assessment criteria. Participants were reviewed at the end of 2 months. Results and conclusions The findings of the observational study show conflict with spouse is the prime reason in majority of diseases (26.9%). Conflict with parents (11.53%), stress at work place (10.57%)and conflict between parents (9.61%) were identified in descending order. It is concluded that Smriti meditation can be a tool in identifying the cardinal psychological reason for psychosomatic symptoms through the subjective revelation to the participant. During the meditation the guide could observe localization of somatic expression of emotions. Also the study observed that the emotional component of the symptom could clear off so that further somatization of the disease can be prevented. Study observed the potential of Smriti meditation in relieving many psychosomatic symptoms like gastrointestinal discomforts, insomnia, head ache, anxiety and depression.